(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In India, the micro, small and medium enterprise (MSME) sector accounts for a major share of industrial production and exports and is considered to generate high employment growth rates. The sector employs around 70 million people and contributes 15% of India’s GDP. A critical role is played by women MSMEs in India. They together generate employment to over 8 million people, with a contribution of 3.09% of industrial output. Yet only one third of early stage entrepreneurs in India are women. Women entrepreneurs face many barriers in setting up and scaling the business – from access to education and training, cultural and legal barriers to major challenge of inadequacy of capital for growth of business. India is rated as third highest in gender gap in entrepreneurship globally. Women’s access to capital is hindered by lack of collateral, credit history and inadequate financial literacy, besides social and cultural biases. The objective of this study is to understand the availability of credit to women owned MSMEs in the country. The study also seeks to draw out the issues and suggests measures to accessing credit. This research paper concludes that the present scenario demands more sincere and significant efforts in the implementation of multiple women entrepreneurship promotion policies and schemes that have been introduced in India. The benefits shall largely escape an individual women entrepreneur till the time they are not taken to the grass root level.